Tau Pathology Profile Across a Parietal-Hippocampal Brain Network Is Associated With Spatial Reorientation Learning and Memory Performance in the 3xTg-AD Mouse - Stimmell, Alina C.; Xu, Zishen; Moseley, Shawn C.; Cushing, Sarah D.; Fernandez, Diana M.; Dang, Jessica V.; Santos-Molina, Luis F.; Anzalone, Rosina A.; Garcia-Barbon, Carolina L.; Rodriguez, Stephany; Dixon, Jessica R.; Wu, Wei; et al. (Frontiers in Aging, 2021)
In early Alzheimer’s disease (AD) spatial navigation is one of the first impairments to emerge; however, the precise cause of this impairment is unclear. Previously, we showed that, in a mouse model of tau and amyloid beta aggregation, getting lost represents at least in part a failure to use distal cues to get oriented in space and that impaired network level plasticity during sleep may underlie this spatial disorientation. We showed that the impaired plasticity during sleep involves a network that includes the parietal cortex and hippocampus. However, the relationship between tau and amyloid beta aggregation in this brain network and impaired spatial orientation has not been assessed. Therefore, we used several approaches, including canonical correlation analysis and independent components analysis tools, to examine the relationship between pathology profile across the parietal-hippocampal brain network and spatial reorientation learning and memory performance. We found that consistent with the exclusive impairment in 3xTg-AD 6-month female mice, only 6-month female mice had an ICA identified pattern of tau pathology across the parietal-hippocampal network that were positively correlated with behavior. Specifically, a higher density of pTau positive cells predicted worse spatial learning and memory. Surprisingly, despite a lack of impairment relative to controls, 3-month female, as well as 6- and 12- month male mice all had patterns of tau pathology across the parietal-hippocampal brain network that are predictive of spatial learning and memory performance. However, the direction of the effect was opposite, a negative correlation, meaning that a higher density of pTau positive cells predicted better performance. Finally, there were not significant group or region differences in M78 density at any of the ages examined and ICA analyses were not able to identify any patterns of 6E10 staining across brain regions that were significant predictors of behavioral performance. Thus, the pattern of pTau staining across the parietal-hippocampal network is a strong predictor of spatial learning and memory performance, even for mice with low levels of tau accumulation and intact spatial re-orientation learning and memory. This suggests that AD may cause spatial disorientation as a result of early intracellular tau accumulation in the parietal-hippocampal network.